Recalibrating retirement spending and saving - Ameriks, John, 1968-; Mitchell, Olivia S. (Oxford : Oxford University Press, 2008)
As baby boomers make the transition into their 60s, they have focused policymakers and the media's attention onto how they will manage the retirement phase of its lifetime. This volume acknowledges that many in this older cohort have accumulated substantial assets, so for them, the question is what will they do with what they have?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Retirement income